2022
DOI: 10.3390/toxics10120778
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and Biotransformation of Chlorinated Paraffins

Abstract: Chlorinated paraffins (CPs), a class of persistent, toxic, and bioaccumulated compounds, have received increasing attention for their environmental occurrence and ecological and human health risks worldwide in the past decades. Understanding the environmental behavior and fate of CPs faces a huge challenge owing to the extremely complex CP congeners. Consequently, the aims of the present study are to summarize and integrate the bioaccumulation and biotransformation of CPs, including the occurrence of CPs in bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 114 publications
(151 reference statements)
0
5
0
Order By: Relevance
“…The above logBAFs and logBSAFs implied the bioaccumulation of SCCPs and MCCPs in zooplankton, crustacea, fish, and invertebrates in Chinese areas. In addition, the bioaccumulation of SCCPs and MCCPs has been observed to have correlations with logKow values, lipid contents, carbon chain length, chlorine atoms, octanol/water partition coefficients, and biotransformation capacity. ,, Besides, studies have shown that demersal marine organisms have higher exposure to CPs than plankton, suggesting a more significant accumulation of CPs in benthic organisms. , …”
Section: Distribution Of Cps In the Marine Environmentmentioning
confidence: 99%
“…The above logBAFs and logBSAFs implied the bioaccumulation of SCCPs and MCCPs in zooplankton, crustacea, fish, and invertebrates in Chinese areas. In addition, the bioaccumulation of SCCPs and MCCPs has been observed to have correlations with logKow values, lipid contents, carbon chain length, chlorine atoms, octanol/water partition coefficients, and biotransformation capacity. ,, Besides, studies have shown that demersal marine organisms have higher exposure to CPs than plankton, suggesting a more significant accumulation of CPs in benthic organisms. , …”
Section: Distribution Of Cps In the Marine Environmentmentioning
confidence: 99%
“…3,4 Chen et al summarized the biological data on CPs published from 1982 to 2022 and found high concentrations of CPs in aquatic and terrestrial organisms from e-waste recycling areas and in plants and animals from Tibet, China. 5 For humans, CPs have been frequently detected in numerous foodstuffs 6−8 and consumer products 9 and can enter the body through ingestion and then spread to organ tissues. 10,11 The concentrations of CPs in these studies ranged from below the detection limit to hundreds or thousands of nanograms per gram of wet weight (ww).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorinated paraffins (CPs) are an important class of environmental contaminants utilized in the production of flame retardants and plasticizers in plastics, rubbers, inks, paints, adhesives, and surface coatings, among other products. They are persistent and ubiquitous in the environment and have been widely found in various abiotic media , and biota. , Chen et al summarized the biological data on CPs published from 1982 to 2022 and found high concentrations of CPs in aquatic and terrestrial organisms from e-waste recycling areas and in plants and animals from Tibet, China . For humans, CPs have been frequently detected in numerous foodstuffs and consumer products and can enter the body through ingestion and then spread to organ tissues. , The concentrations of CPs in these studies ranged from below the detection limit to hundreds or thousands of nanograms per gram of wet weight (ww).…”
Section: Introductionmentioning
confidence: 99%
“…3,5 CPs have been considered as a global threat due to their ubiquitous existence, persistence, bioaccumulation and potential adverse health effects. 1,[6][7][8] CPs are widely distributed in various environmental media such as air, 9,10 water, 11 sediment, 12 soil 9,13 and biota. 14,15 CPs have been detected in the Arctic Ocean, indicating long-range transport.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Bioaccumulation and biomagnication of SCCPs, MCCPs and LCCPs are reported in aquatic and/or terrestrial food webs. 6,18,19 Toxicological studies indicated that SCCP exposure can lead to liver and renal toxicity, 2,20 embryotoxicity, 21,22 endocrine and metabolic disruption 21,23 and immunomodulatory effects 24,25 in various organisms or cell lines. But the toxicity of MCCPs and/or LCCPs is extremely rare.…”
Section: Introductionmentioning
confidence: 99%